2020
DOI: 10.1017/s1047951120002668
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of Konar-multifunctional occluder

Abstract: Introduction: Lifetech Konar-multifunctional occluder is a novel device which is primarily used for the closure of ventricular septal defects. Being “multifunctional”, the occluder has the potential to be useful in various structural cardiac defects. Materials and methods: We share our retrospective review from two centres regarding non-conventional usage of multifunctional occluders in CHD. Eight patients who underwent interventions using multifunctional occluders for lesions other than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…These devices can be deployed with a smaller diameter guiding catheter or long sheath. Mukherji et al [22] found in their study that it may be possible to use a sheath or guide catheter one French size smaller than the manufacturer's recommended size. Device with screws on both sides adds to the technical advantage of placement.…”
Section: Discussionmentioning
confidence: 98%
“…These devices can be deployed with a smaller diameter guiding catheter or long sheath. Mukherji et al [22] found in their study that it may be possible to use a sheath or guide catheter one French size smaller than the manufacturer's recommended size. Device with screws on both sides adds to the technical advantage of placement.…”
Section: Discussionmentioning
confidence: 98%
“…However, the specific challenges related to the perimembranous location of the defect made the intervention complex, and device-related complications were not infrequent pushing interventionists to abandon some of the devices (20). Cumulative experience showed that ADOII and the more recently introduced MFO both appear to be adequate double-disk devices for this intervention, particularly for retrograde implantation (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Herein, we present a comprehensive comparison of the outcomes of these two devices in retrograde pmVSD closure and detail the fate of encountered complications.…”
Section: Discussionmentioning
confidence: 99%
“…Amplatzer TM duct occluder II (ADOII) (Abbott Cardiovascular, USA), a device designed for arterial duct closure, and the more recent KONAR-MF TM VSD occluder (MFO) (Lifetech, China) are convenient double-disk occluders for retrograde approach with interesting characteristics (Figure 1) (9)(10)(11). The safety and short-term efficacy of these two devices for pmVSD closure have been described in separate cohorts by us and others (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). We expand upon these earlier findings and comprehensively evaluate the midterm outcomes of our experience with retrograde closure using these two devices.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Lifetech™ Konar-MFO is a relatively newer and versatile device which has shown promising results in both perimembranous and muscular ventricular septal defects along with selected cases of patent ductus arteriosus. 20 Lifetech™ Konar-MFO has the advantage of double screwing hub which makes using the retrograde approach possible despite it is not a symmetrical device. 10 The main advantage of the retrograde approach is that the aortic valve is kept safe, no snare is needed in the equipment and thus no need to form an AV loop, which significantly cuts down on fluoroscopy time and thus general anesthesia time.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its conventional use as VSD occluder, the versatility of the device allows its use in patent ductus and coronary fistula also. 11 The present study describes our experience with using Lifetech™ Konar-MFO in our centre over the past three years. The findings of this study will give us an opportunity to compare the outcome of using Lifetech™ Konar-MFO with other occluders, help us improve our current practices and serve as a local study for other cardiac centres in the country.…”
Section: Introductionmentioning
confidence: 99%